The impact of liquidity management on profitability of commercial banks in Malaysia / Muhammad Amir Aiman Kamil - Kamil, Muhammad Amir Aiman (2022)
The aim of this research is to identify the effects of liquidity risk management on commercial bank profitability in Malaysia. The research is performed using Return on Assets (ROA) to examine the relationship between Current Ratio (CR), Cash Deposit Ratio (CDR) and Loan to Total Deposit Ratio (LDR) to bank profitability. Information for this analysis were collected from the sampled companies' related databases and annual reports. This study uses secondary data from six (6) conventional banks listed in Bursa Malaysia between the year 2016 to 2020. This study uses panel data to examine the collected data. The results of this study are focused on descriptive analysis, correlation analysis, and regression analysis.